Prevalence of rheumatic diseases among city dwellers of Dnestr region of Republic Moldova - V. A. Sokolov (Сеченовский вестник, 2018)
It is conducted researches of frequency of rheumatic diseases among 4000 people of the organised and unorganized populations of inhabitants of Tiraspol. On the ﬁrst place in structure rheumatic diseases is оsttoartrit which relative density makes 60.0%, on the second place - an revmatic arthritis - 7%, on the third place - spondilo arthritis - 6%. The gout - of 5.5%, jet arthritises of 3.0% and system defeats of a connecting fabric - 1.4% Further has settled down. Thus оsteoartrit it was deﬁned with frequency of 10.1% of cases, revmatic arthritis - 0.3%, a gout of 0.22%, jet arthritise arthritis - 0.03%, the spondilo arthritis - 0.04% and system defeats of a connecting fabric - 0.10%, etc. At comparison of the received data about frequency rheumatic diseases in Dnestr region Moldova with the data of similar researches in the Russian Federation have been established that they approximately correspond to the data across the Russian Federation. Besides almost at everythird patient with rheumatic diseases (32.4%) were deﬁned signs abnormal connective tissue , and meteorticulate a syndrome the obtained data allows to put forward the assumption of interrelation rheumatic diseases with, abnormal connective tissue which presence, most likely, causes a spectrum accompanying rheumatic diseases somatic diseases.